Extractable Al and Soil Solution Ionic Concentrations in Strongly Leached Soils from Northwest Iberia: Effects of Liming. (2nd May 2012) - Auxtero, Edgardo; Madeira, Manuel; Parker, David
Abstract : Strongly leached soils occurring in Northwest Iberia contain high concentration of Al which may affect crop growth. Information regarding the extractability of Al and lime required to eliminate toxic Al species in the soil solution is scarce. In this context, the extractability of Al on these soils was determined using 1 M KCl, 0.33 M LaCl3 and 0.5 M CuCl2 . The effects of lime on the concentration and activity of Al species in soil solution, using the GEOCHEM program was also evaluated. Extractability of Al was in the order: 1 M KCl < 0.33 M LaCl3 < 0.5 M CuCl2, with ranges from 0.7–3.3, 1.3–4.4, and 1.8–13.5 cmolc kg −1, respectively. These values were positively correlated with cation exchange capacity and organic C, clay, Alo and Feo contents. Application of 6 t CaCO3 ha −1 increased the total concentrations of Ca +2, Mg +2, K +, and Na + ions in soil solution, whereas, application of 2 t CaCO3 ha −1 reduced the concentration and activity of Fe +3, Al +3, Mn +2, Zn +2, Cu +2, SO 4 - 2, andPO 4 - 3 ions, and eliminated toxicity threshold of free Al +3 and Al soluble complexes in the soil solution. Application of low amounts of lime may prevent the negative effects of soluble Al on crops.